Daya Hasil Galur-Galur Kacang Tanah (Arachis hypogaea L.) Tahan Penyakit Bercak Daun di Kecamatan Ciranjang Kabupaten Cianjur Provinsi Jawa Barat - Yudiwanti Wahyu; Dede Rosyana Budiman (Buletin Agrohorti, 2013)
This research was aimed to evaluate the yield of 16 peanut leafspot resistant lines derived from cross between Gajah variety and GPNC-WS 4 line with four check varieties of peanut. The four check varieties of peanut consist of Gajah, Jerapah, Zebra Putih, and Sima. The experiment was carried out at Ciranjang District, Cianjur Regency, West Java, from February to May 2011. This research was arranged in randomized complete block design with three replications. Result showed that GWS 39 D, GWS 110 D, GWS 18 A1, GWS 79 A, and GWS 110 A2 were identified as lines with high yield. GWS 74 D, GWS 39 B, GWS 79 A, GWS 73 D, GWS 18 A1, GWS 134 A1, and GWS 110 A1 were identified as lines with high resistant level to leafspot of peanut. Two of sixteen lines had high yield and high resistant level to leafspot, they were GWS 79 A and GWS 18 A1.Key words : peanut, yield evaluation, leaf spot resistant